2014
DOI: 10.1371/journal.pone.0110341
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of G3 Rotavirus Strains Circulating in Argentina during 1998–2012 Assessed by Full Genome Analyses

Abstract: Seasonal shifts in the predominant strains and the periodic emergence of new strains are epidemiological features of human rotaviruses. After the sporadic detection in two samples in 1998, G3P[8] strains reemerged as the predominant rotavirus during 2008–2009 in Argentina. Notably, in 2011 6.3% (37/587) of samples presented the G3P[6] genotypes, which coincided with the recent detection of G3P[6] and G2P[6] strains in South America and Europe. Analyses of the 11 gene segments of four G3P[8] and two G3P[6] stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…The RV vaccine have been shown to improve the health and well-being of children in countries where it has been introduced [ 47 , 48 , 49 , 50 ], leading to rapid and substantial drops in hospitalization and deaths due to RV infections [ 51 , 52 , 53 ]. Although the immunity induced by the vaccine protects against severe RV disease, re-infections by different genotypes of RV can occur throughout life as these viruses have a high genetic diversity [ 54 , 55 , 56 ]. This is a concern as several studies have reported the emergence of new RV strains that are not covered by the vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The RV vaccine have been shown to improve the health and well-being of children in countries where it has been introduced [ 47 , 48 , 49 , 50 ], leading to rapid and substantial drops in hospitalization and deaths due to RV infections [ 51 , 52 , 53 ]. Although the immunity induced by the vaccine protects against severe RV disease, re-infections by different genotypes of RV can occur throughout life as these viruses have a high genetic diversity [ 54 , 55 , 56 ]. This is a concern as several studies have reported the emergence of new RV strains that are not covered by the vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Residues of our G3P[9] differed most from the vaccine, particularly on the 7-1b antigenic epitope. Interestingly, the K238N substitution, which is also present in various G3 strains from Argentina, Belgium, Pakistan, and Lebanon [ 16 , 17 , 61 63 ], can potentially introduce an N-linked glycosylation in the 7-1b epitope and reduce antibody neutralization [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The broad host range for G3 including feline, canine, equine, porcine, lapine, bovine, rats, rhesus, and bats has resulted in the occasional detection of animal-like RVA infection in patients with diarrhea [ 14 , 19 24 ]. Although G3 is often found in combination with P[8], P[4], and P[6], pairings with P[9] and P[10] are less frequently reported [ 17 , 21 , 25 29 ]. Previously, we conducted surveillances of RVA infection in Thailand from 2015 to 2019 and found that G3 strains were most predominantly detected in adults and children with viral diarrhea [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic tree was constructed using neighbor joining method (with 1000 bootstrap replicates) and distances were calculated with Kimura 2-parameter method using MEGA 5 [ 38 ]. Lineage designation for phylogenetic trees of G3 and P[8] were based on criteria reported earlier [ 19 , 39 ]. Structural analysis of VP7 (PBD 3FMG) and VP8* (PDB 1KQR) were performed using the UCSF Chimera-Molecular Modeling System [ 40 ].…”
Section: Methodsmentioning
confidence: 99%